Proceedings of the 12th ACM SIGMETRICS/PERFORMANCE Joint International Conference on Measurement and Modeling of Computer Syste 2012
DOI: 10.1145/2254756.2254810
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of the random replacement policy for networks of caches

Abstract: The overall performance of content distribution networks as well as recently proposed information-centric networks rely on both memory and bandwidth capacities. In this framework, the hit ratio is the key performance indicator which captures the bandwidth / memory tradeoff for a given global performance. This paper focuses on the estimation of the hit ratio in a network of caches that employ the Random replacement policy. Assuming that requests are independent and identically distributed, general expressions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Cache networks first became a subject of interest as a means to improve the performance of the Web [7,27], and work on ICN architectures has renewed interest in this topic [4,6,16,[22][23][24][25][26]33].…”
Section: Cachingmentioning
confidence: 99%
See 1 more Smart Citation
“…Cache networks first became a subject of interest as a means to improve the performance of the Web [7,27], and work on ICN architectures has renewed interest in this topic [4,6,16,[22][23][24][25][26]33].…”
Section: Cachingmentioning
confidence: 99%
“…This consideration is so pervasive that many research papers (e.g., [16,21,23,29,33]) use the notion of "cache network" as an abstraction to describe "content-centric networks".…”
Section: Architectures and Systemsmentioning
confidence: 99%
“…Most of them consider LRU replacement policy. However, most of them only consider a single cache scenario, such as [23,24], and only few works consider a network of caches, such as [25]. Among these works, [26] studied the miss sequence of LRU cache replacement policy, and provides an analytical characterization of the miss probability and miss rate under Poisson assumptions of content requests' arrivals from the viewpoint of caching.…”
Section: Related Workmentioning
confidence: 99%
“…LRU is the most frequently used one in the literature, although it is observed that simple random cache replacement can also approximate the performance of LRU [22].…”
Section: Related Workmentioning
confidence: 99%